2012
DOI: 10.1111/j.1478-3231.2012.02847.x
|View full text |Cite
|
Sign up to set email alerts
|

QT interval prolongation by acute gastrointestinal bleeding in patients with cirrhosis

Abstract: Acute gastrointestinal bleeding further prolongs QTc in cirrhosis. This abnormality independently predicts bleeding-induced mortality. The combined measurement of QTc interval and MELD can clearly identify three patient strata at increasing risk of bleeding-related mortality, thus improving the decision-making for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 23 publications
5
38
0
3
Order By: Relevance
“…Genovesi et al demonstrated a significant correlation between the stage of cirrhosis according to the Child-Pugh classification, the hepatic venous pressure gradient (HVPG) and QT interval prolongation, which was more common in patients with alcoholic than viral cirrhosis [13]. QT interval prolongation independently predicts bleedinginduced mortality in patients with cirrhosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Genovesi et al demonstrated a significant correlation between the stage of cirrhosis according to the Child-Pugh classification, the hepatic venous pressure gradient (HVPG) and QT interval prolongation, which was more common in patients with alcoholic than viral cirrhosis [13]. QT interval prolongation independently predicts bleedinginduced mortality in patients with cirrhosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a sudden increase in this activity caused by acute gastrointestinal bleeding further lengthens this time interval with potential adverse outcomes. Trevisani et al [73] showed that in a group of cirrhotic patients with this complication, the QT interval lengthened at the time of bleeding and all those that died had a longer QTc than survivors. In addition, QTc was able to independently predict survival, with a best cut-off value of ≥ 460 ms.…”
Section: Gastrointestinal Bleedingmentioning
confidence: 99%
“…In the presence of ion channel alteration (as stated above), the influence of sympathetic activity on QT interval might be different from normal individuals. This hypothesis was supported by the increased risk of cardiac arrhythmia with elevated sympathetic activity in patients with type 1 and 5 long QT syndromes, who possessed mutant genes coding for delayed rectified potassium channels in the heart [59]. Moreover, a sudden rise in sympathetic tone could transiently prolong QTc interval as shown in a recent study in cirrhotic patients with acute gastrointestinal (GI) bleeding [60].…”
Section: Clinical Manifestation and Pathophysiologic Processmentioning
confidence: 99%